2009
DOI: 10.2105/ajph.2007.127530
|View full text |Cite
|
Sign up to set email alerts
|

Legal Barriers to Second-Trimester Abortion Provision and Public Health Consequences

Abstract: Many women need access to abortion care in the second trimester. Most of this care is provided by a small number of specialty clinics, which are increasingly targeted by regulations including bans on so-called partial birth abortion and requirements that the clinic qualify as an ambulatory surgical center. These regulations cause physicians to change their clinical practices or reduce the maximum gestational age at which they perform abortions to avoid legal risks. Ambulatory surgical center requirements signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Electric and manual vacuum technologies appear to be equally effective; however, the use of manual vacuum aspiration is associated with less pain in pregnancies under 9 weeks' gestation and with more procedural difficulty over 9 weeks' gestation (57). Vacuum aspiration under 14 weeks' gestation is more effective and associated with fewer minor complications than medical abortion (56,58).…”
Section: Vacuum Aspiration Vacuum Aspirationmentioning
confidence: 99%
See 2 more Smart Citations
“…Electric and manual vacuum technologies appear to be equally effective; however, the use of manual vacuum aspiration is associated with less pain in pregnancies under 9 weeks' gestation and with more procedural difficulty over 9 weeks' gestation (57). Vacuum aspiration under 14 weeks' gestation is more effective and associated with fewer minor complications than medical abortion (56,58).…”
Section: Vacuum Aspiration Vacuum Aspirationmentioning
confidence: 99%
“…One methodology that has been used effectively is the WHO Strategic Approach to strengthening sexual and reproductive health policies and programmes (55)(56)(57)(58)(59)(60). The Strategic Approach begins with the creation of an assessment team representing a broad range of stakeholders, such as those mentioned above, who conduct a field-based assessment to identify and prioritize needs related to abortion and contraceptive-service access, availability and quality of care.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that more than 90% of the state's population resides in urban locations, with most residents living in the Boston area (U.S. Census Bureau, 2000). Finally, almost all of the women included in this study obtained firsttrimester abortion care; the experiences of women seeking abortion after the first trimester, when access is likely more limited (Jones & Weitz, 2009), are not reflected here.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The net effect was that there was a 68 percent decrease in the number of abortions at 16 weeks or later performed on Texas residents one year after the law took effect. Similarly, Jones and Weitz [40] reported that a TRAP law enacted in Mississippi in 2005, requiring that second-trimester abortion providers must comply with all ambulatory surgical center regulations, caused the only outpatient abortion provider in Mississippi to stop providing abortions after 12 weeks of gestation resulting in many unwanted births.…”
Section: Trap Lawsmentioning
confidence: 99%